Healthcare-associated Gram-negative bloodstream infections: antibiotic resistance and predictors of mortality. Issue 4 (December 2016) - Ergönül, Ö.; Aydin, M.; Azap, A.; Başaran, S.; Tekin, S.; Kaya, Ş.; Gülsün, S.; Yörük, G.; Kurşun, E.; Yeşilkaya, A.; Şimşek, F.; Yılmaz, E.; et al.
Summary: This article describes the prevalence of antibiotic resistance and predictors of mortality for healthcare-associated (HA) Gram-negative bloodstream infections (GN-BSI). In total, 831 cases of HA GN-BSI from 17 intensive care units in different centres in Turkey were included; the all-cause mortality rate was 44%. Carbapenem resistance in Klebsiella pneumoniae was 38%, and the colistin resistance rate was 6%. Multi-variate analysis showed that age >70 years [odds ratio (OR) 2, 95% confidence interval (CI) 1.22–3.51], central venous catheter use (OR 2.1, 95% CI 1.09–4.07), ventilator-associated pneumonia (OR 1.9, 95% CI 1.1–3.16), carbapenem resistance (OR 1.8, 95% CI 1.11–2.95) and APACHE II score (OR 1.1, 95% CI 1.07–1.13) were significantly associated with mortality.